Quem tem medo do processo coletivo? As disputas e as escolhas políticas no CPC/2015 para o tratamento da litigiosidade repetitiva no Brasil - Miranda, Andrea Pimentel de (2019)
It is a consensus among Brazilian jurists that the Judiciary is going through a crisis that affects its ability to act with efficiency and quality, distancing itself from a minimally satisfactory model of justice. In this scenario, repetitive litigation acquires special relevance insofar as it is identified as one of the main problems faced by the Judiciary. Observing the way to deal with the effects of repetitive litigation by the Code of Civil Procedure of 2015, the question that guides the present work arises: why repetitive case judgment techniques - specifically the Brazilian case management technique “Incidente de Resolução de Demandas Repetitivas”- were preferred by the legislator? The main idea is to analyze documents related to the elaboration of the Code of Civil Procedure of 2015 (minutes of meetings and public hearings, news, text of the draft, substitutes and amendments), seeking to observe how the legislative process took place, especially the choice for enlargement of the technique of trial of repetitive cases to deal with repetitive litigiousness, while the collective process occupied the role of supporting actor as a technique capable of dealing with the same question. In addition, it seeks to understand who the actors were responsible for this choice and what were its justifications.